2013
DOI: 10.1111/ibi.12122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flipper bands and injected transponders on the survival of adult Little Penguins Eudyptula minor

Abstract: Tagging is essential for many types of ecological and behavioural studies, and it is generally assumed that it does not affect the fitness of the individuals being examined. However, the tagging of birds has been shown to have negative effects on some aspects of their lives. Here we investigate the influence of tagging on apparent survival. We examined the effects of flipper bands and injected transponders on the apparent survival of adult Little Penguins by comparing the survival probabilities of 2483 Little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 49 publications
1
17
1
Order By: Relevance
“…However, any bias is probably of the order of magnitude reported by Dann et al . () of around 5% rather than the larger biases reported in other genera (e.g. up to 30% in Saraux et al .…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…However, any bias is probably of the order of magnitude reported by Dann et al . () of around 5% rather than the larger biases reported in other genera (e.g. up to 30% in Saraux et al .…”
Section: Discussioncontrasting
confidence: 53%
“…, Dann et al . , but see Appendix S1). Long‐term double‐marking studies on African Penguins have not been carried out and efforts are now in place to discontinue flipper‐banding of this species (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of effects of logger position in little penguins, logger size in Adélie penguins and, surprisingly, flipper bands in little penguins suggests that animal-attached devices do not universally induce such organizational changes in seabird foraging behavior, despite having clear effects on other dive parameters and potentially, for flipper bands at least, fitness outcomes [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, dive durations and betweendive durations increased in the flipper band experiment, meaning that the sequential distribution and variance of both dive and surface durations may not have changed, leaving the global structure of the foraging trip unchanged as well. This also suggests that global structural changes in the organizational complexity of dive sequences need not be associated with other changes in foraging behavior, e.g., those induced by flipper bands, that are known to significantly affect survival and reproduction (e.g., [49][50][51]). …”
Section: Discussionmentioning
confidence: 99%
“…While they have a large breeding distribution, Gentoo penguins also exhibit high levels of natal philopatry and tend to remain within the same archipelagos year-round (Stonehouse 1970;Tanton et al 2004;Ratcliffe and Trathan 2011). However, determining the limits of the species' foraging range over a lifetime is difficult because of ethical, cost, and technical challenges associated with long-term tag or transponder use (Froget et al 1998;Gauthier-Clerc et al 2004;Saraux et al 2011;Dann et al 2014). Previous studies have indicated that Gentoo penguins have a maximum observed dispersal of 276 km during the nonbreeding season in the Falkland Islands (Clausen and P€ utz 2003) and 268 km in the South Shetland Islands (Wilson et al 1998).…”
Section: Introductionmentioning
confidence: 99%